Traces of Solidarity in Liberation Training Sites in Angola - (:unkn) unknown (My University, 2023)
Angola from the mid-1970s until the late 1980s hosted guerrillas fighting for the liberation of other southern African states, as well as Cuban and Soviet military advisors and civilian professionals. As the study of Cold War–era liberation struggles has developed from nation-centred narratives towards both global and local perspectives, the international encounters that took place in the ambit of these struggles have attracted historians’ attention. In particular, the military training camp has come to be seen as an environment that nurtured specific kinds of social and political relationships, yet little physical evidence of these camps remains. This article is based on photographs taken at Camalundu and Caculama, two sites in Angola’s Malanje province where the remains of camps are still visible. At Camalundu, Portuguese colonial architecture points to the site’s original function, while slogans painted in English and Spanish, variously referencing South African history and global revolutionary movements, speak of the presence of Cubans and South Africans and provide evidence of how they saw their own role within the international politics of the day. At Caculama the secluded and defensive nature of the site and its installations provides evidence of the South African role in relation to Angolan strategic thinking. The photographs complement the existing memoirs and oral testimony about the politics of exile and about life in the camps, to provide evidence of different kinds about the presence of liberation fighters and their relationships with the wider world. They also serve to preserve a visual and tangible historical record which, in the absence of preservation measures, is in danger of decay beyond recognition.
Keywords: African Research